Penguatan Pemahaman Thoharoh dalam Kajian Kitab Safinatunnajah di Desa Asemgede Jombang - Ashoumi, Hilyah; Hariono, Tholib; Sirojudin, Didin; Santoso, Moh Hilmi; Bajuri, Mohammad Fahim; Yani, Meista Dwi; Safitri, Ika Rahma; Kholisoh, Nur (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2024)
Thoharoh, or purification, is one of the essential elements in Islamic teachings and a fundamental requirement for the validity of worship, especially prayer. However, based on observations in Asemgede Village, there is a gap in understanding the proper procedures for thoharoh among the community. Therefore, this community service activity aims to enhance the knowledge of mosque and musholla congregants in the village through the study of fiqh from the book Safinatunnaja. The methods used include lectures, discussions, Q&A sessions, and hands-on practice. This activity was carried out in collaboration between LPPM UNWAHA, KUA Ngusikan, and local religious leaders. The results show a significant improvement in participants' understanding of thoharoh procedures, as indicated by the pre- and post-activity survey results. This program is expected to strengthen religious understanding and improve the quality of worship in Asemgede Village. Additionally, a product in the form of a thoharoh guidebook was produced, which is easy for congregants to study and aims to enhance daily religious practices.